Square-wave voltammetric determination of rutin in pharmaceutical formulations using a carbon composite electrode modified with copper (II) phosphate immobilized in polyester resin - Kellen Heloizy Garcia Freitas; Orlando Fatibello-Filho; Ivanildo Luiz de Mattos (Universidade de São Paulo, 2012)
A carbon composite electrode modified with copper (II) phosphate immobilized in a polyester resin (Cu3(PO4)2-Poly) for the determination of rutin in pharmaceutical samples by square-wave voltammetry is described herein. The modified electrode allows the determination of rutin at a potential (0.20 V vs. Ag/AgCl (3.0 mol L-1 KCl)) lower than that observed at an unmodified electrode. The peak current was found to be linear to the rutin concentration in the range from 9.9 × 10-8 to 2.5 × 10-6 mol L-1, with a detection limit of 1.2×10-8 mol L-1. The response of the electrode was stable, with no variation in baseline levels within several hours of continuous operation. The surface morphology of the modified electrode was characterized by scanning electron microscopy (SEM) and energy dispersive X-ray (EDX) system. The results obtained are precise and accurate. In addition, these results are in agreement with those obtained by the chromatographic method at a 95% confidence level. Descreve-se um eletrodo de carbono modificado com fosfato de cobre (II) imobilizado em uma resina de poliéster (Cu3(PO4)2-Poly) para a determinação de rutina em amostras farmacêuticas por voltametria de onda quadrada. O eletrodo modificado permite a determinação de rutina em potencial (0.20 V vs Ag / AgCl (3,0 mol L-1 KCl)) menor que o observado em um eletrodo não modificado. Verificou-se que a corrente de pico foi linear com a concentração de rutina na faixa de 9,9 × 10-8 a 2,5 × 10-6 mol L-1, com um limite de detecção de 1,2 × 10-8 mol L¹. A resposta do eletrodo foi estável, sem variação significativa dentro de várias horas de operação contínua. A morfologia da superfície do eletrodo modificado foi caracterizada por microscopia eletrônica de varredura (MEV) e pelo sistema de energia dispersiva de raios-X (EDX). Os resultados obtidos foram precisos e exatos. Ademais, estes resultados estão de acordo com aqueles obtidos pelo método cromatográfico a um nível de confiança de 95%.